2022
DOI: 10.3389/fphar.2021.811818
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Efficacy of an Antioxidant Compound on Blood Retinal Barrier Breakdown and Visual Dysfunction in Streptozotocin-Induced Diabetic Rats

Abstract: In diabetic retinopathy (DR), high blood glucose drives chronic oxidative stress and inflammation that trigger alterations of the neurovascular balance finally resulting in vascular abnormalities and retinal cell death, which converge towards altered electroretinogram (ERG). In the last years, a growing body of preclinical evidence has suggested that nutrients with anti-inflammatory/antioxidant properties can be able to hamper DR progression since its very early stages. In the present study, we used a streptoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…In conclusion, we have shown here in an in vitro model system with human microvascular retinal endothelial cells that the association of two polyphenols (C3G and verbascoside), belonging to different families, may efficiently prevent the endothelial barrier dysfunction that usually follows diabetic hyperglycemic stress, and is the cause of diabetic retinopathy progression towards the most dangerous proliferative neovascular stage. These data confirm and further support from a biological point of view what had already been shown in an in vivo model system of early-stage diabetic retinopathy [45,46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, we have shown here in an in vitro model system with human microvascular retinal endothelial cells that the association of two polyphenols (C3G and verbascoside), belonging to different families, may efficiently prevent the endothelial barrier dysfunction that usually follows diabetic hyperglycemic stress, and is the cause of diabetic retinopathy progression towards the most dangerous proliferative neovascular stage. These data confirm and further support from a biological point of view what had already been shown in an in vivo model system of early-stage diabetic retinopathy [45,46].…”
Section: Discussionsupporting
confidence: 90%
“…The better efficacy of the mixture on the dysfunctional electroretinogram was also demonstrated by the improved rod and cone photoreceptor responses [45]. More pertinent to the goal of this study is the efficacy shown by the oral administration of the association of C3G, verbascoside and zinc on the diabetic retinopathy induced in rats by streptozotocin treatment [46]. This in vivo preclinical study reported a dose-dependent inhibition of oxidative stress-related and inflammation-related mechanisms in the retina of diabetic rats, with a significant reduction of DR-associated vasculopathy and its related retinal damage.…”
Section: Introductionmentioning
confidence: 89%
“…These nutrients have been related to better neuronal plasticity, and reduced gliosis and oxidative stress, and appear to maintain neurogenesis and blood-brain barrier integrity in in vitro studies and animal models. [50][51][52] Further, the MIND diet pattern also limits high saturated fat, high-sugar foods, and red and processed meats. Saturated fats and sugars may induce neuroinflammation by mediating mitrogen-activated protein kinase and nuclear factor kappa B signaling pathways, negatively impacting BDNF pathways and increasing blood-brain barrier permeability in the hippocampus causing synaptic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MIND diet is also rich in other essential nutrients, such as long‐chain omega‐3 fatty acids from fish and nuts; B vitamins from vegetables and whole grains; and vitamin K and lutein from green leafy vegetables. These nutrients have been related to better neuronal plasticity, and reduced gliosis and oxidative stress, and appear to maintain neurogenesis and blood–brain barrier integrity in in vitro studies and animal models 50–52 . Further, the MIND diet pattern also limits high saturated fat, high‐sugar foods, and red and processed meats.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in models of induced diabetes in rodents, the retina exhibits a pro-inflammatory profile [ 14 ]. Retinal inflammation may furthermore be causally related to the development of DR, since application of several anti-inflammatory compounds dampened retinal dysfunction in rodent models of diabetes [ 16 , 17 , 103 ]. Inflammation may also be an important modulator in the development of ROP.…”
Section: Ischemic Retinopathiesmentioning
confidence: 99%